The Use of Smart Tree Learning Media to Improve Arabic Writing Skills for Class X - Hazhiyah Luthfi Lubis; Akmal Walad Ahkas (Universitas Pahlawan Tuanku Tambusai, 2022)
This study was structured with the aim of describing the improvement of students' writing skills by using the smart tree learning media in class X Man 1 Deli Serdang. This type of research is Classroom Action Research (CAR). This research was conducted in the even semester of TA. 2021/2022, i.e. in March-April. The subjects of this study were students of class X MAN 1 Deli Serdang which consisted of 25 students. The object of this research is the students' writing ability. This research data collection was collected using a test that had been given to the students. Based on the results of the student learning percentage test in the first cycle was 71.32% and the result in the second cycle was 81.08%. From the results of the comparison of the two cycles, there was an increase of 9.76%. The use of the Smart Tree learning media can improve students' Arabic writing skills in the